IMF Engagement with Countries in Post-Conflict and Fragile Situations : Stocktaking. (Policy Papers; Policy Paper ;, 2015)
This review examines experience in implementing the lessons drawn in the 2011 Board paper on the Fund's engagement with countries in post-conflict and fragile situations (more commonly referred to as fragile states (FS)) and the ensuing 2012 Guidance Note. The focus is on capacity building, Fund facilities and program design, and policy support. The review identifies scope to improve the Fund's engagement in selected areas.